2023
DOI: 10.1038/s41598-023-37695-9
|View full text |Cite
|
Sign up to set email alerts
|

A perceptual field test in object experts using gaze-contingent eye tracking

Abstract: A hallmark of expert object recognition is rapid and accurate subordinate-category recognition of visually homogenous objects. However, the perceptual strategies by which expert recognition is achieved is less known. The current study investigated whether visual expertise changes observers’ perceptual field (e.g., their ability to use information away from fixation for recognition) for objects in their domain of expertise, using a gaze-contingent eye-tracking paradigm. In the current study, bird experts and no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…In the face domain, preschool teachers and maternity ward nurses, who benefit from prolonged visual experience with child and newborn faces, respectively, display similar hallmarks of holistic processing when presented with adult and child/infant faces, while novices show stronger holistic effects for own-age faces [37,38,82]. In the non-face domain, behavioral markers of holistic perception have been reported for people with extensive real-world experience discrimination objects within a domain (i.e., domain experts), including car experts recognizing cars [83], chess experts recognizing chess-board configurations [84], bird watchers recognizing birds [85], and in laboratory-trained experts recognizing artificial objects [86]. Moreover, it has been shown that discrimination training with novel objects is more effective when the stimuli to be learned have face-like configurations [87].…”
Section: Discussionmentioning
confidence: 95%
“…In the face domain, preschool teachers and maternity ward nurses, who benefit from prolonged visual experience with child and newborn faces, respectively, display similar hallmarks of holistic processing when presented with adult and child/infant faces, while novices show stronger holistic effects for own-age faces [37,38,82]. In the non-face domain, behavioral markers of holistic perception have been reported for people with extensive real-world experience discrimination objects within a domain (i.e., domain experts), including car experts recognizing cars [83], chess experts recognizing chess-board configurations [84], bird watchers recognizing birds [85], and in laboratory-trained experts recognizing artificial objects [86]. Moreover, it has been shown that discrimination training with novel objects is more effective when the stimuli to be learned have face-like configurations [87].…”
Section: Discussionmentioning
confidence: 95%
“…Next, to further characterize the size Stroop effect (incongruentcongruent), it was analyzed in an exploratory analysis as a function of how quickly participants responded. This analysis allows for testing whether the conflicting familiar-size knowledge influenced both fast and slow responses during the orthogonal screen-size task, inspired by previous work testing conflict effects on both fast and slow RTs (e.g., Ridderinkhof, 2002) and work examining how visual object knowledge (e.g., object color and shape) contributes to expert object recognition (Hagen et al, 2014(Hagen et al, , 2016(Hagen et al, , 2023. The faster the conflicting familiar-size knowledge is processed in parallel, the more likely it is to influence fast reaction times.…”
Section: Discussionmentioning
confidence: 99%